The Innovation Path of Industry-Education-Research Integration from The Perspective of The Psychological Relationship of School Enterprise Cooperation - Jianping Feng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Industry-education-research cooperation is one of the important paths for the application and transformation of current efficient technological achievements. Based on the perspective of school-enterprise partnership psychological cooperation, this study deeply explores the construction path of China's current Industry-education-research integration and innovation system, so as to achieve the goal of promoting the deep integration of Industry-education-research and the application and transformation of key core technology innovation capability in universities. Based on this, based on the advanced experience of Industry-education-research integration and innovation in American enterprises, this study compares and analyzes the current reality of school-enterprise cooperation in China and the unique role played by large state-owned or central enterprises in this process. It is found that from the perspective of partnership psychology, Chinese universities, research institutions, different types of private enterprises and service intermediary institutions all have obvious deficiencies in the process of Industry-education-research partnership cooperation, while large state-owned or central enterprises have strong comparative advantages under the current market system and industry background in China. Therefore, centering on the establishment of "university + State-owned enterprise" partnership-oriented Industry-education-research integration innovation system, this study gives policy development suggestions from multiple perspectives, and brings effective guidance for the formation of new scientific and technological innovation industrial cycle.